Implementation of KIA Indicator Information System Web Based in Gunung Sindur Health Center, Bogor: Implementation of KIA Indicator Information System Web Based in Gunung Sindur Health Center, Bogor - Jejen Jaenudin; Gibtha Fitri Laxmi; Puspa Eosina; Yuggo Afrianto (Jurnal Mantik, 2020)
The Gunung Sindur Public health centre in its work area handles several villages, each of which has a number of Posyandu cadres in the village. Posyandu activities in addition to providing information about health, also facilitate the community in obtaining health services for mothers, infants and toddlers. In this activity, each village midwife must make a monthly report that is recorded in the cohort book to produce an evaluation as a reference to follow up the performance development activities, and the PWS-KIA calculation process is still done using conventional counting tools that are reported to the Puskesmas coordinator midwife and after it was reported to the Bogor District Health Office as a monitoring target and target for mothers and children so that in the storage of the MCH reporting archives it appeared to be poorly documented. Therefore, this research analyzes and develops a reporting information system to make it easier for coordinating midwives and village midwives to calculate monitoring indicators and document them. The research method for system development uses the waterfall method which consists of analysis, design, programming, and testing. The results of this study developed a web-based KIA indicator information system in the Gunung Sindur Bogor Puskesmas, input data will be processed automatically and presented quickly and neatly in the form of tables and graphs.